Effects of diet and Gemfibrozil on posttransplant hyperlipidemia in renal transplant recipients - (:unkn) unknown (BMJ Publishing Group, 2009)
Background: Posttransplant hyperlipidemia increases cardiovascular morbidity and mortality rate in renal transplant recipients. It also leads to graft loss due to atherosclerosis and glomerular damage. It is essential to control hyperlipidemia in renal transplant recipients to prevent these events. Methods: In our study, we determined lipid profiles in 59 renal transplant recipients. Twenty of the recipients had hyperlipidemia; 9 had type IV, and 11 had type II hyperlipoproteinemia. Randomly selected 14 of 20 hyperlipidemic patients consisted of the diet group and were treated with American phase 3 diet for 1 month. Randomly selected 6 of the 20 hyperlipidemic patients received their regular diet as the control group. Five diet-resistant patients in the American phase 3 diet group were given diet plus placebo for another 1 month and then they were given diet plus Gemfibrozil (600 mg twice a day) for 2 months. Results: Lipid profile was normalized in 9 of the 14 patients on American phase 3 diet. The lipid profile of 5 patients in the American phase 3 diet group did not change significantly after 1-month diet. These 5 diet-resistant patients were given diet plus placebo for another 1 month, and their lipid levels again did not change significantly. Afterward, they were treated with Gemfibrozil (600 mg twice a day) plus American phase 3 diet for 2 months. At the end of this therapy period, their cholesterol level and triglyceride level decreased significantly. No change was observedin low-density lipoprotein cholesterol and high-density lipoprotein cholesterol levels. Conclusions: We conclude that American phase 3 diet and/or Gem-fibrozil are effective in controlling posttransplant hyperlipidemia in renal transplant recipients. Copyright © 2009 by The American Federation for Medical Research.
Keywords: American phase 3 diet; Gemfibrozil; Hyperlipidemia; Renal transplantation